Analisis Strategi Peningkatan Penjualan Pulsa pada Usaha Sela Mantap - Shella Aprilia; Benedikta Kiky Puspitasari; Sabinus Beni; Veneranda Rini Hapsari (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to provide an overview of the implementation of Sela Mantap's business both before and after the growth of product sales. This research uses interviews and is qualitative. The research subjects were selected using a purposive sampling technique totaling 5 people. The data collection technique in this study uses observation, interviews, and documentation. Data analysis was carried out qualitatively consisting of data reduction, data presentation and conclusion drawing. The results of data analysis show that consumers with marketing tactics used by business actors to offer services and promote Sela Mantap business to customers. Based on the results of the research, it can be seen that there are several techniques used, one of which is increasing sales of Sela Mantap. The 4P marketing strategy implemented by Sela Mantap business actors has a significant impact on the daily services provided to measure customer satisfaction with the sale of Sela Mantap goods, namely the 4P promotion strategy, location, product, and price.